Levofloxacin and Ibuprofen Leading to Steven Johnson Syndrome: A Dermatological Emergency - Muhammad Raheel Zafar,Mohsin Ahmed,Muhammad Sharjeel Sabir (Journal of Rawalpindi Medical College, 2018)
Stevens-Johnson syndrome is a rare, serious disorder of your skin and mucous membranes. It’s usually a reaction to a medication or an infection. Often, it begins with flu-like symptoms, followed by a painful red or purplish rash that spreads and blisters. Then the top layer of the affected skin dies, sheds and then heals.Stevens-Johnson syndrome is a medical emergency that usually requires hospitalization.1 Treatment focuses on eliminating the underlying cause, controlling symptoms and minimizing complications as skin regrows. Recovery after Stevens-Johnson syndrome can take weeks to months, depending on the severity of condition. If it was caused by a medication, you’ll need to permanently avoid that drug and others closely related to it.